SISTEM PELAPORAN PENCATATAN AKUNTANSI ATAS PENDAPATAN PAJAK KENDARAAN BERMOTOR DENGAN MENGGUNAKAN METODE CASH BASIS PADA LAYANAN SAMSAT KELILING - Turini, Turini; Hatta, Muhammad; Fanisa, Nur (Fakultas Ekonomi dan Bisnis, 2024)
AbstractRegional Revenue Management Center for Kab. Cirebon 1 Sumber is the center of an organization or agency that is under the local government which has responsibility for receiving regional revenues through coordinating and collecting taxes, levies, tax sharing, balancing funds and others. This study aims to design, implement, analyze, and implement.The data collection methodology used in a study is observation. The system used in this application program is PHP (Hypertext Preprocessor) as the web, MySQL as the database design, using the Google Chrome browser and using a cash-based method (cash basis). In reporting daily receipts at the central office for regional revenue management in the Cirebon Regency, 1 source is still using the manual, namely using HVS paper, there is accumulation of files, data recording errors, and in making reports less efficient and effective. cirebon 1 source is illustrated by using a running flowchart accompanied by explanatory narration, then made computerized into a flowmap to be applied to the system so as to minimize the occurrence of human errors, file stacking, lost data, to be more efficient and effective. Keywords: Income, Motor Vehicle Tax, Cash Basis, Mobile Samsat